Intraoperative Raman‐Guided Chemo‐Photothermal Synergistic Therapy of Advanced Disseminated Ovarian Cancers. Issue 31 (4th July 2018) - Zhang, Yuqing; Liu, Zhiyang; Thackray, Benjamin D.; Bao, Zhouzhou; Yin, Xia; Shi, Fenglei; Wu, Jianbo; Ye, Jian; Di, Wen
Abstract : Abdominal miliary spread and metastasis is one of the most aggressive features in advanced ovarian cancer patients. The current standard treatment of advanced ovarian cancer is cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC). However, most patients cannot receive optimal CRS outcomes due to the extreme difficulty of completely excising all microtumors during operation. Though HIPEC can improve prognosis, treatment is untargeted and may damage healthy organs and cause complications. New strategies for precise detection and complete elimination of disseminated microtumors without side effects are therefore highly desirable. Here, cisplatin‐loaded gap‐enhanced Raman tags (C‐GERTs) are designed specifically for the intraoperative detection and elimination of unresectable disseminated advanced ovarian tumors. With unique and strong Raman signals, good biocompatibility, decent plasmonic photothermal conversion, and good drug loading capacity, C‐GERTs enable detection and specific elimination of microtumors with a minimum diameter of 1 mm via chemo‐photothermal synergistic therapy, causing minimal side effects and significantly prolonging survival in mice. The results demonstrate that C‐GERTs‐based chemo‐photothermal synergistic therapy can effectively control the spread of disseminated tumors in mice and has potential as a safe and powerful method for treatment of advanced ovarian cancers, to improve survival and life quality of patients. Abstract : Cisplatin‐loaded gap‐enhanced Raman tags (GERTs) are designed for the intraoperative detection and elimination of unresectable disseminated advanced ovarian tumors. It is demonstrated that GERTs‐based chemo‐photothermal synergistic therapy can effectively control the spread of disseminated tumors in mice and has potential as a safe and powerful method for treatment of advanced ovarian cancers.